Evaluasi efektivitas tanaman repelen dalam pengendalian penggerek batang Apomecyna saltator F. (Coleoptera: Cerambycidae) pada tanaman labu madu dengan pola tanam tumpang sari: Evaluation of the effectiveness of repellent plants in controlling stem borers Apomecyna saltator F. (Coleoptera: Cerambycidae) on honey pumpkin plants with intercropping patterns - Salsabilla, Fitria; Wilyus; Siregar, Hamdan Maruli (Jurnal Entomologi Indonesia, 2023)
Apomecyna saltator Fabricius (Coleoptera: Cerambycidae) is a pest of honey pumpkin plants whose presence is increasingly more economically important. However, information about this pest is still very limited. Control by application of intercropping patterns has prospects and needs to be developed further. Control of this pest should be an integral part of the development of integrated pest management. This research was conducted to determine the effect of intercropping pattern of honey pumpkin plants with several repellent plants on percentage of infestation, population of A. saltator larvae/pupae, and honey pumpkin production. This study was designed with a randomized block design (RBD) consisting of 4 treatments, namely: honey pumpkin plants monoculture (A); intercropping of honey pumpkin and lemon grass plants (B); intercropping of honey pumpkin and turmeric plants (C); intercropping of honey pumpkin and spring onion plants (D). Each treatment was repeated 6 times. The results show that; the average percentage of infestation by A. saltator until 56 days after planting (DAP) for all treatments ranged from 72–79.6%. The population of A. saltator larvae/pupae ranged from 107–128 individuals/9 plants. Honey pumpkin production ranged from 21.97–26.75 kg/9 plants. From the results it was concluded that turmeric, lemon grass, and spring onions had no effect on the percentage of infestation of A. saltator populations, and honey pumpkin production.